Concepts of money and decisions about its use in Tweens - Denegri C., Marianela (2013)
The purpose of this research was to determine the possible relationship among consumption habits (use of money, decisions about its use and ideas about money), socioeconomic status and gender on tweens. The sample was constituted by 468 participants from city of Temuco, Chile, their ages range between 10 and 14. We applied the Consumer Habits Questionnaire (Denegri, Lara, Cordova, and Del Valle, 2008). The results indicate statistically significant relationships between NSE and use of money, decision of use and ideas about money. The information complements the observed in previous studies. A longitudinal study is suggested to observe the evolution of these habits over time.